Exploring definitions of Indigenous student success - Milne, Emily; Wotherspoon, Terry (My University, 2022)
Bringing together twenty-one articles written by experts, Social Inequality in Canada explores the many dimensions of social disadvantage and injustice that exist in this country today. Beginning with a thorough examination of structural inequality issues before moving on to address the wide-ranging impact that social inequality can have, the text presents students with a comprehensive overview of both the persistent patterns of inequality as well as the progress that has been made.
Keywords: Indigenous peoples -- Education -- Canada; classroom management; Indigenous peoples; equality -- Canada; Canada -- Social conditions -- 1991-; social classes